Analysis of the Influence Physical Education on Character Development of Elementary School Students - Ilham Kamaruddin; Nugroho Susanto; I Putu Agus Dharma Hita; Emy Yunita Rahma Pratiwi; Dindin Abidin; Antonia Junianty Laratmase (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
This study aims to analyze the impact of physical education on character development in elementary school students. Recognizing the significance of physical education in shaping student character from a young age, this research seeks to explore how the development of positive character traits can aid students in navigating future challenges and life situations. The methodology employed in this study involves a comprehensive literature review, drawing data from reputable sources such as scientific journals, books, and relevant articles. Content analysis techniques are utilized to analyze the data and identify key factors contributing to the influence of physical education on students' character development. The findings demonstrate that physical education plays a crucial role in fostering desirable character traits, including discipline, hard work, self-confidence, cooperation, and more. Furthermore, physical education also contributes to improving students' physical and mental well-being. Based on the results of the analysis, it can be concluded that physical education significantly influences the character building of elementary school students. Consequently, the integration of physical education into the school curriculum becomes imperative to ensure the holistic development of students, promoting good character and overall health.